Timothy Mortons øko-kristne vision af himmel og helvede - Albinus, Lars (Dansk Teologisk Tidsskrift, 2025)
Widely acclaimed philosopher Timothy Morton discloses that after having been involved with Tantric Buddhism for 40 years they (i.e., Morton) have recently become born-again-Christian. That personal note aside, they offer a challenging vision of the connection between Christianity and ecology in their latest book Hell: In Search of a Christian Ecology (2024). Loosely framed as an interpretation of – and thinking together with – William Blake’s work, Morton brings their own commitment to an object-oriented-ontology to bear on a drama between heaven and hell, appreciating the earth’s biosphere as the sacred reference for Christ’s announcement of the divine kingdom “to be at hand”. Christian ecology is, according to Morton, the faith in a future that is different from the Anthropocene’s hellish biotope of deluge and conflagration. The leading question of the present article is in what sense Morton’s ecological thinking attains a certain profile through their Christian self-understanding?